Exploring Challenges And Opportunities In Implementing Mother Tongue-Based Multilingual Education In Arunachal Pradesh’s Tribal Communities (Journal of Namibian Studies : History Politics Culture, 2023)
Arunachal Pradesh, located in the linguistically diverse North East region of India, represents a critical case study in the implementation of mother tongue-based multilingual education (MTB-MLE). Home to over 26 major tribes and more than 100 sub-tribes, the state faces unique challenges in integrating indigenous languages into formal schooling, particularly through the development and use of tribal language textbooks. This paper examines the status, quality, and pedagogical alignment of third-language textbooks introduced at the primary level in five tribal languages: Idu Mishmi, Kaman Mishmi, Wancho, Galo, and Nyishi. Employing a qualitative framework, the study analyses the textual content, instructional design, linguistic standardization, and cultural relevance of these materials. Findings reveal both progress and persistent gaps: while textbook creation reflects growing institutional and community engagement, it suffers from inconsistencies in pedagogical structure, lack of assessment tools, and inadequate dialectal representation. These issues are compounded by broader policy-level disparities, where national commitments to mother tongue education are undermined by limited infrastructure, inadequate teacher training, and the continued dominance of English and Hindi. The study argues for a shift from symbolic to substantive inclusion of indigenous languages through centralized academic support, inclusive curriculum design, and community co-authorship. Ultimately, the paper contributes to the discourse on linguistic justice, educational equity, and the preservation of endangered languages in India’s tribal regions by highlighting the need for culturally grounded and pedagogically sound approaches to textbook development. Without systemic reforms and sustained policy attention, the transformative potential of mother tongue education in Arunachal Pradesh risks remaining unrealized.